PENGARUH PENGELUARAN PEMERINTAH SEKTOR PUBLIK TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Putri Setyawati Wahyuningrum; Whinarko Juliprijanto (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research examines the effect of government expenditure on education, health, infrastructure, agriculture, and transportation on economic development in Indonesia between 1981 and 2020. This research uses yearly data (time series) taken from the Revenue and Expenditure Budget of the Indonesian Ministry of Finance. State Budget (APBN) and World Bank funds. Error Correction Model (ECM) is used to identify the long-term and short-term correlations between each variable in the data analysis approach. According to the findings of the study, there are no significant variables affecting economic growth over the short term; however, over the long term, government spending on the education sector has a positive and significant effect on economic growth, whereas government spending on the infrastructure sector has a negative and significant effect on economic growth. In the meantime, the factors that decide how much the government spends on sectors such as education, health, infrastructure, agriculture, and transportation have a major effect on the pace of long- and short-term economic growth.